2021
DOI: 10.1002/ejhf.2288
|View full text |Cite
|
Sign up to set email alerts
|

Post‐discharge arrhythmic risk stratification of patients with acute myocarditis and life‐threatening ventricular tachyarrhythmias

Abstract: The outcomes of patients presenting with acute myocarditis and life-threatening ventricular arrhythmias (LT-VA) are unclear. The aim of this study was to assess the incidence and predictors of recurrent major arrhythmic events (MAEs) after hospital discharge in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
1
27
0
2
Order By: Relevance
“…In keeping with prior studies, we identified anteroseptal LGE [23][24][25][26] and histological signs suggesting chronic myocarditis [12,13] as factors associated with adverse arrhythmic outcomes, both in the whole cohort and in patients without malignant VA onset. Results are consistent with recently published data [27]. As suggested by Table 3, mild systolic dysfunction (i.e., LVEF < 50%) may play an additional role for primary prevention risk stratification, as already suggested both in myocarditis and other cardiomyopathies [28,29].…”
Section: Arrhythmic Risk Estimationsupporting
confidence: 92%
“…In keeping with prior studies, we identified anteroseptal LGE [23][24][25][26] and histological signs suggesting chronic myocarditis [12,13] as factors associated with adverse arrhythmic outcomes, both in the whole cohort and in patients without malignant VA onset. Results are consistent with recently published data [27]. As suggested by Table 3, mild systolic dysfunction (i.e., LVEF < 50%) may play an additional role for primary prevention risk stratification, as already suggested both in myocarditis and other cardiomyopathies [28,29].…”
Section: Arrhythmic Risk Estimationsupporting
confidence: 92%
“…Specifically, ~40% of patients presenting with life-threatening VA can experience a recurrence at a median time of 8 months based on a recent international registry including 156 patients ( 104 ). Factors associated with arrhythmic recurrence were initial presentation with sustained VT, LGE involving ≥2 myocardial segments, and absence of T2-weighted short-tau inversion recovery (STIR) signal suggestive for residual edema on CMRI ( 104 ). In this registry, 98 patients underwent EMB showing in the large majority of cases a lymphocytic myocarditis (88.8%).…”
Section: Specific Subset Of Myocarditismentioning
confidence: 99%
“…In this registry, 98 patients underwent EMB showing in the large majority of cases a lymphocytic myocarditis (88.8%). An immunosuppressive therapy was initiated in 21% of cases and there was no difference in the use of immunosuppressive therapy between patients who subsequently experience an arrhythmic recurrence vs. those who did not ( 104 ). A second registry of 185 patients with VA (including VF/VT, non-sustained VT, and Lown's ≥2 premature ventricular complexes [PVC]) and myocarditis confirmed a 30% of recurrence of malignant VA at 2 years ( 105 ).…”
Section: Specific Subset Of Myocarditismentioning
confidence: 99%
“…Outcomes of acute myocarditis are not clearly defined. 3,22,23 A total of 466 consecutive patients, with clinically suspected or biopsy-proven myocarditis, were enrolled in a single centre prospective study from 1992 to 2012. Survival free from death or heart transplantation at 10 years was 83% and was lower in biopsy-proven versus clinically suspected myocarditis (76% vs. 94%, p < 0.001).…”
Section: Acute Myocarditismentioning
confidence: 99%